New Technology for Inclusive and Sustainable Growth Perception, Challenges and Opportunities - Inshakova, Elena I.; Inshakova, Agnessa O.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book offers a multidisciplinary investigation into the economic, technological, environmental, and social impacts of Industry 4.0 technology that ensures inclusive and sustainable growth development of regions and countries. Along with identifying new opportunities that new technology provides for inclusive growth, the book aims to propose theoretical substantiation and develop economic, institutional, organizational, and information mechanisms that aid to reduce and eliminate the potential economic, social, and environmental risks. A broad multidisciplinary approach integrating research capabilities of economic and administrative sciences, artificial intelligence and computer sciences, pedagogy and linguistics, latest findings in the above mentioned scientific areas, as well as empirical evidence and pilot innovative research projects conducted by the contributors, allowed them to draw conclusions and develop recommendations for achieving inclusive growth in industrial and agricultural production, innovation and investment activities, management and environment protection, healthcare and education associated with the use of new technology. The contributors hope that empirical materials, innovative developments, and suggestions inspire scientific research, encourage applied studies, and supplement training programs in economic, administrative, social, and computer sciences at the advanced universities and research institutions, in the post-Soviet territory, in particular.
Systemic factors and prerequisites for the inclusive growth of the Russian economy -- High-Tech Economic Growth from the Standpoint of the Theory of Economic Time: Modeling and Reducing Space-Time Inequality -- Innovative technologies as a factor in ensuring inclusive growth in the unified ecosystem of urban and rural areas -- Adaptation potential of inclusive growth of the regions of the South of Russia in the context of the COVID-19 pandemic -- The success model to manage the cross-border infrastructure projects -- Digital transformation of managing business entities development in agricultural production -- Decarbonization trends in the largest post-soviet countries and the specifics of their inclusion in the global climate agenda -- Ensuring the openness of environmentally relevant information as an environmental component of inclusive growth of Russia$1 (Bs regions -- The development of inclusive economy based on digital technologies: econometric assessment of formation -- Digital transformation of the national economic system: identification of key determinants.s
Keywords: Industrial Management; Artificial intelligence; Blockchains (Databases).; Industrial Management; Artificial Intelligence; Blockchain; Industry 4.0.; Sustainable development; Technological innovations